2020
DOI: 10.1111/jam.14816
|View full text |Cite
|
Sign up to set email alerts
|

A new multidrug‐resistant enterotoxigenic Escherichia coli pulsed‐field gel electrophoresis cluster associated with enrofloxacin non‐susceptibility in diseased pigs

Abstract: Aims To describe the temporal trends in Escherichia coli pathotypes and antimicrobial resistance detected in isolates from diseased‐pig cases submitted to the EcL from 2008 to 2016, in Quebec, Canada, and to investigate the presence of spatiotemporal and phylogenetic clusters. Methods and Results Detection of 12 genes coding for virulence factors in pathogenic E. coli in pigs by PCR and antimicrobial resistance standard disc diffusion assay were performed. Demographic and clinical data were entered in the Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…We demonstrated that the clone A-I appeared in 2013 and became predominant in 2015 (data from this study and [ 16 ]), consequently meeting the emergence criteria (cf Table 1 ). The clonality of ETEC isolates from various states of the USA and belonging to clonal lineage A had already been demonstrated [ 20 ].…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…We demonstrated that the clone A-I appeared in 2013 and became predominant in 2015 (data from this study and [ 16 ]), consequently meeting the emergence criteria (cf Table 1 ). The clonality of ETEC isolates from various states of the USA and belonging to clonal lineage A had already been demonstrated [ 20 ].…”
Section: Discussionsupporting
confidence: 67%
“…Although our data demonstrate the capacity of WGS to refine the analysis for detecting clones, they also show that the combination of MLST and serotype data can accurately discriminate clonal lineages. On the other hand, when we compared these results to those obtained with PFGE in our previous study, we observed that only two thirds of the isolates analyzed with both methods were classified correctly by the PFGE when the cut-off of 55% of similarity was used to define a cluster [ 16 ]. Price et al found a similar misclassification for the E. coli ST131 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations